Pengaruh Sikap Siswa Terhadap Hasil Belajar Matematika Melalui Kombinasi Model Pembelajaran Kooperatif - Lambertus .; Miasih Ambarsari; Faad Maonde (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo,, 2016)
This experimental study employs factorial 2x3 design with the aims are to: (i) describe the students’ Maths achievement at SMPN 2 Konawe Selatan (ii) to describe the effects of students’ attitude on their Maths achievement, (iii) describe the difference of score average of Maths achievement for all cells formed by cooperative learning models (Ai) and students’ attitude (Bj), (iv) describe the diffrenece of Maths achievment of students among students’ attitude level factors (Bj) for every factor level of cooperative learning models (Ai), (v) describe the differennce of average score among the cooperative learning models factors (Ai) for every students’ attitudes (Bj) and (vi) describe the difference of Maths achievement between all model factors of cooperative learning models (Ai) and students’ attitude (Bj). The analysis result: the students’ attitude have significant positive effect on students’ Maths achievement, the combination of cooperative models of TSTS-NHT is found more effective than TSTS cooperative learning model and the best attitude of the students is better than moderate and is better than less good attitude.